Distinct subtypes of proprioceptive dorsal root ganglion neurons regulate adaptive proprioception in mice - Haohao Wu (Nature Portfolio, 2021)
Molecular diversity of proprioceptive neuron types (Ia, Ib and II PNs) is unclear. Here, the authors characterized the functional organization and development of eight subtypes of PNs in mice. Importantly, Ia subtypes are plastic, suggesting a role in adaptive proprioception during motor behavior.